Correlation relation between professional qualifications of physical education teachers and students' attitudes towards Physical Education classes - E. Sucuoglu; H. Atamturk (IP Iermakov S.S., 2020)
Purpose: This empirical study investigated the impact of the professional qualifications of Physical Education (PE) teachers on secondary school students' attitudes towards their PE classes. Education in general and teaching and learning in particular are multidimensional phenomena and thus it is essential to determine and define these dimensions to sustain quality in education. From the psychological perspective, along with various factors, teachers' personality and qualifications may affect students' learning process. In this respect, effective teachers can foster students' learning process and help develop positive attitudes towards a course. Material: In order to fulfill the research aim, the data were elicited through a questionnaire from five hundred and ninety-two secondary school students from grades 9, 10 and 11in North Cyprus to be analyzed quantitatively. Kolmogorov-Smirnov Test and Shapiro-Wilk Testwere run to test normality. Seeing that the data set was not well-modeled by a normal distribution, a Spearman's rank correlation coefficient was run to measure the association between the variables. Results: A very strong positive correlation was found between the professional qualifications of teachers and the participants' attitudes towards PE classes. Conclusions: The results indicated that there was a significant relationship between the qualifications of the teachers and the students' attitudes towards PE classes. More specifically, it was found that the higher the perceptions of students of the professional qualifications of PE teachers, the more positive attitudes they developed towards PE classes.